Linguistic Credibility in Digital Academia: The Role of Politeness and Hedging in Peer Endorsed Responses - Hermansyah, Sam; Faradillah, Nurul; Linuwih, Endar Rachmawaty; Yelnim; Aditiawarman, Mac (Lingua : Journal of Linguistics and Language, 2025)
Politeness and hedging are central in shaping credibility and interpersonal dynamics in online academic communication. This study examines how these strategies affect persuasion in Q&A forums, particularly Academia and CrossValidated communities on Stack Exchange. It aims to measure their influence on persuasive success through three indicators: answer acceptance, scoring, and response timing. Drawing on a corpus of 20,000+ threads, the study applies computational tools to detect politeness markers and hedging terms. The analysis uses mixed effects logistic regression, negative binomial regression, and Cox proportional hazards models, while controlling for user reputation, message length, and thread depth. Results show that politeness and hedging significantly enhance persuasive outcomes. Posts with more polite and mitigative language are more likely to be accepted, receive upvotes, and get faster responses. The effects are stronger for users with lower reputation, indicating that politeness functions as a compensatory strategy in digital peer interactions. The discussion acknowledges the limits of automated detection tools and stresses the role of context, culture, and disciplinary norms in interpreting politeness and hedging. This study concludes that politeness and hedging are essential rhetorical resources in digital academic dialogue. The findings offer practical implications for AI-driven moderation and feedback systems that aim to support inclusive and effective scholarly communication.